Especificidad de la planta hospedadora y preferencia alimentaria de larvas de Morpho epistrophus argentinus (Lepidoptera: Nymphalidae) en bosques costeros de Argentina - Carro, Mariana Emilia (2019)
The selection of suitable host plants for larval development is critical for most herbivorous insects. In this study, we examined host plant preferences of larvae from Epistrophus white morpho butterfly, Morpho epistrophus argentinus (H. Fruhstorfer), a specialized butterfly that oviposits on a few plant species. In many species, the selection of host plant for larvae development is under the control of ovipositing females and the role of larvae in host selection is minimal. At field, we characterized larval host plant use in coastal woodland patches of its southernmost distribution range (36º 25’ S, 56º 57’ W; Argentina). All sampled M.e. argentinus larvae groups (n = 40) were found on Scutia buxifolia trees, although the number of larval groups did not correlate with cover of this plant at patch scale. Translocation experiments showed that M.e. argentinus larvae translocated to unsuitable host plants had a shorter residence time than those translocated to suitable (i.e. control) hosts. Choice assays made also indicated strong feeding preferences of wild larvae for S. buxifolia leaves. The results highlight the high degree of host specificity of M.e. argentinus by S. buxifolia, and reveal that growing larvae preference for host plant matches that of ovipositing females.